The meaning and significance of non-club talent development environments from the perspective of elite football players - Söderström, T. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Adult football success in Sweden can, besides the training in the club, be advanced through the Swedish football associations regional (U15-17) and national (U15-U21/23) team systems or through elite sport schools at the upper secondary school. These systematic talent development environments are of central interest in this study. Research on talent development environments has had a focus on football academies and environmental success factors (e.g., Cooper, 2021; Larsen et al, 2013). However, to date, research undertaken has not in any greater extent taken into consideration non-club environments and athletes views on how useful those environments have been for their development into elite football players. Thus, in this paper the aim is to explore the meaning and significance of non-club talent development environments by scrutinizing elite football players experiences of participating in such environments and their importance for their development as football players.